Preparation and validation of nanomolar aqueous bilirubin standard solutions - Paola Sist; Federica Tramer; Ranieri Urbani; Antonella Bandiera; Sabina Passamonti (MethodsX, 2025)
Bilirubin (BR) is the product of cellular heme catabolism and the main bile pigment in animal blood. It is an established biomarker for hemolysis and liver function. Over the last decade, mild hyperbilirubinemia has been shown to be a biomarker for a lower risk of cardiovascular disease, due to its antioxidant and anti-inflammatory effects. In order to use bilirubin as a predictive biomarker, new powerful methods for its direct analysis in human blood are currently being developed. To harmonize the different methods, it is essential to use high-quality BR standard solutions for assay calibration. We present here a protocol for the preparation of stable standard solutions in the range of 10−9- 10−5M BR at pH 7.4 that can facilitate a uniform approach for assay calibration without or with a sample preparation step. • The bilirubin standard solutions are prepared in buffered saline solution at physiological pH (not in alkali, not in apolar solvents) added with BSA • The standard solutions are in a wide range of concentrations. • The preparation has a quality control procedure based on direct analysis of bilirubin UV–VIS spectra or fluorescence emission of the its complex with the recombinant fusion protein HELP-UnaG (HUG).